Pattern and prevalence of dental anomalies among a paediatric population in Lagos, Nigeria - Olatosi, Olubukola; Oyapero, Afolabi; Akinwande, Kehinde; Ayedun, Oladipupo; Aladenika, Emmanuel; Obe, Olorunfemi (The Nigerian postgraduate medical journal, 2022)
Background: Dental anomalies are craniofacial abnormalities in the size, structure or number of the teeth. This study was conducted to assess the prevalence of dental anomalies among children aged 0-16 years attending the Paediatric Dental Clinic at the Lagos University Teaching Hospital, Lagos, Nigeria. Methods: A cross-sectional design was used and data were obtained from the dental records of the Dental Clinic from January 2014 to August 2019 by two calibrated examiners, who are co-authors of the manuscript. To test for statistical differences, Chi-squared test was utilised for the categorical variables. The prevalence of the different dental anomalies was estimated and presented with frequencies. P < 0.05 was considered statistically significant. Results: Among the 6175 patients' dental records reviewed, 50.85% (n = 3150) were male and the highest proportion of 45.4% (n = 2807) were aged between 6 and 10 years, with a mean age of 8.62 ± 3.85 years. A total of 1090 (17.52%) had dental anomalies; 465 (7.53) anomalies were in the maxilla, 263 (4.6) were in the mandible while 360 (5.83) were in both. The most common anomaly was hypoplasia 550 (9.06%), followed by retained primary tooth 546 (8.84%) and hypodontia 84 (1.36%). Dentinogenesis imperfecta 1 (0.02) and transposition 1 (0.02) were the least prevalent anomalies. Retained primary teeth (5.8%) and the cusp of Carabelli (0.4%) were slightly more prevalent among males. However, females had a higher prevalence of natal/neonatal teeth (0.4%), fusion/germination (0.4%), hypodontia (1.5%) and peg-shaped lateral incisors (0.9%). Conclusion: Dental anomalies' prevalence in this study was 17.52%, with a higher occurrence of anomalies in the maxilla. Hypoplasia was the most prevalent anomaly, after which was retained primary tooth, then hypodontia. Prompt diagnosis and preventive interventions are crucial for the appropriate management of these dental anomalies.